Perlindungan Hukum terhadap Debt Collector yang Melakukan Pengambilan Kendaraan Bermotor Objek Jaminan Kredit - Abd Rohman (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2017)
Humans as social beings need the help of other humans in meeting their daily needs. In meeting these needs, one of the ways used is to buy goods in a non-cash manner. However, often the payment is not smooth, so as an effort then the creditor/lessee using debt collector to take seizure or seizure of motor vehicles. The conclusions of this paper are: (1) the legal relationship between the debt collector and the debtor that is the debt collector in performing his work acts as a lessor based on a power of attorney given by the lessor to the debt collector to collect or take forcibly the collateral object from the debtor, as provided in Article 1792 and Article 1795 Civil Code concerning special power of attorney; and (2) the legal protection of debt collector taking the motor vehicle of credit guarantee object can be applied if the debt collector in conducting its action does not violate the provisions of Article 368 of the Criminal Code (extortion); in addition, in the lease agreement there is a clause which excludes Article 1266 Civil Code , so retrieval of the lease object does not require a judge's verdict.